PATTERN OF NEONATAL ADMISSION AT THE CHILDREN’S HOSPITAL AND THE INSTITUTE OF CHILD HEALTH, MULTAN - Quddusi, Ahmed Iqbal; Razzaq, Athar; Hussain, Sajjad; Hussain, Afaq (Journal of Ayub Medical College Abbottabad, 2012)
Background: Neonatology is a rapidly growing paediatric sub-specialty all over the world. Neonatal disease pattern changes from time to time and place. Analyzing the neonatal admission pattern helps the policy makers to make the better strategies and health care givers to serve better. Method: This was a descriptive study. The study data was collected of the patient admitted in neonatal unit of Children Hospital Complex and Institute of Child Health, Multan, Pakistan from 1st January 2010 to 31st December 2010. The data of all the admitted neonates was analysed according to their causes of admission in whole one year whether admitted through emergency department or OPD clinic. Result: Total numbers of neonatal admissions were 3,560. Birth asphyxia was found to be major cause of admission, 1,230 patients (34.5%). Among infections, sepsis was found in as a whole in 1,009 (28.3%) of admission, pneumonia in 170 (4.7%) and meningitis in 30 (0.8%). Out of 3,560 patients admitted, 2,550 were discharged after improvement, 290 died, and 720 left against medical advice (LAMA). Conclusion: Birth asphyxia, sepsis and prematurity are the main reasons for admission in neonatal age. By paying good attention to perinatal services, we can reduce morbidity and mortality in neonates. Keywords: Neonates, Birth asphyxia, Sepsis